2021
DOI: 10.1177/2472555220976126
|View full text |Cite
|
Sign up to set email alerts
|

A “Target Class” Screen to Identify Activators of Two-Pore Domain Potassium (K2P) Channels

Abstract: Two-pore domain potassium (K2P) channels carry background (or leak) potassium current and play a key role in regulating resting membrane potential and cellular excitability. Accumulating evidence points to a role for K2Ps in human pathophysiologies, most notably in pain and migraine, making them attractive targets for therapeutic intervention. However, there remains a lack of selective pharmacological tools. The aim of this work was to apply a “target class” approach to investigate the K2P superfamily and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Potassium two pore domain channel subfamily K member 1 (KCNK1) is a widely expressed pH-gated two pore structural domain potassium channel, often encoding TWIK-1 or K2P1 protein[ 12 , 13 ]. KCNK1 plays an important role in physiological and pathological functions associated with changes in electrical membrane potential by controlling the efflux of potassium ions to maintain the balance of the resting potential of the cell membrane [ 14 , 15 ]. Previous research indicated that KCNK1 plays a very vital role in promoting tumour cell malignant transformation, especially in regulating cell cycle progression and cancer cell malignant proliferation and migration [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potassium two pore domain channel subfamily K member 1 (KCNK1) is a widely expressed pH-gated two pore structural domain potassium channel, often encoding TWIK-1 or K2P1 protein[ 12 , 13 ]. KCNK1 plays an important role in physiological and pathological functions associated with changes in electrical membrane potential by controlling the efflux of potassium ions to maintain the balance of the resting potential of the cell membrane [ 14 , 15 ]. Previous research indicated that KCNK1 plays a very vital role in promoting tumour cell malignant transformation, especially in regulating cell cycle progression and cancer cell malignant proliferation and migration [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the siRNA knock-down of TREK-2 increased pain behaviors under skin inflammation [ 58 ]. TRAAK knockout mice also showed sensitivity to mechanical and heat stimuli [ 59 ] and postsurgical neuropathic pain [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the TREK channels could be attractive targets for the development of novel therapeutics. Despite the recent development of activators and inhibitors targeting the TREK channels [ 60 ], further investigation of the potent and/or selective pharmacological tools for the TREK channels is awaited [ 26 ]. In this respect, although not a direct activator by itself, the strong facilitation by Ech A suggests a novel type of pharmacological tool for modulating the TREK channels.…”
Section: Discussionmentioning
confidence: 99%